2021
DOI: 10.1111/liv.14801
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Chinese patients with hepatitis B at 96 weeks after functional cure with IFN versus combination regimens

Abstract: Background & Aims Nucleotides with add‐on interferon treatment (NUC‐IFN) provide significantly higher rates of hepatitis B surface antigen (HBsAg) loss in patients with chronic hepatitis B (CHB). This study aimed to investigate the sustainability of HBsAg loss and the prevention of clinical relapse. Methods Patients with CHB who achieved HBsAg loss and HBV DNA levels <20 IU/ml after IFN or NUC‐IFN therapy were enrolled and followed up for 96 weeks. The primary outcome was HBsAg negativity without viremia at we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 24 publications
2
30
1
Order By: Relevance
“…However, multiple recent studies have definitively demonstrated that HBsAg clearance induced by peg-IFNα was durable during long-term follow-up and the incidence of HCC was extremely low (<1.5%) in HBV clinically cured patients. [27][28][29][30][31] Furthermore, even some patients were not clinically cured, a full course of peg-IFNα treatment also induced favourable outcomes during long-term follow-up, including HBsAg clearance and no disease progression. 32 The long-term effectiveness data collection of this study is ongoing, and the subsequent results will also be reported in the future.…”
Section: Study Limitationsmentioning
confidence: 99%
“…However, multiple recent studies have definitively demonstrated that HBsAg clearance induced by peg-IFNα was durable during long-term follow-up and the incidence of HCC was extremely low (<1.5%) in HBV clinically cured patients. [27][28][29][30][31] Furthermore, even some patients were not clinically cured, a full course of peg-IFNα treatment also induced favourable outcomes during long-term follow-up, including HBsAg clearance and no disease progression. 32 The long-term effectiveness data collection of this study is ongoing, and the subsequent results will also be reported in the future.…”
Section: Study Limitationsmentioning
confidence: 99%
“…The functional cure of CHB has been considered as a feasible clinical treatment goal, 7,8 which is correlated with improved clinical outcomes. 9 Nevertheless, only a small proportion of patients reach this milestone. 10,11 The complex interaction between HBV and the host immune system drives the process of chronic HBV infection, in which the anti-HBV adaptive immune system processes facilitate the clearance of HBV.…”
Section: Introductionmentioning
confidence: 99%
“…The functional cure of CHB has been considered as a feasible clinical treatment goal, 7 , 8 which is correlated with improved clinical outcomes. 9 Nevertheless, only a small proportion of patients reach this milestone. 10 , 11 …”
Section: Introductionmentioning
confidence: 99%
“…Chen et al revealed that entecavir and pegylated interferon-alpha-2a add-on therapy has no impacts on the shortterm improvement of liver histology of patients with chronic hepatitis B in China, where the major HBV genotype was genotype C [7]. Combination therapy may contribute to long-term improvement of liver histology compared with NUC monotherapy [10]. Further investigations regarding the mechanism of interferon signaling pathways and the effects in the combination of pegylated interferon and NUCs on HBsAg loss, suppression of hepatocarcinogenesis, and the longer-term observation of liver histology or elastography should be conducted.…”
Section: Abbreviationsmentioning
confidence: 99%